(untitled) (Journal of Governance and Development (JGD), 2014)
The role of parliament in a budget process in an important issue in the public financial management. The extent of the parliament to exercise control in determining budget appropriations affects the flexibility of spending units in utilizing their budget optimally. This paper looks at the budgetary role of the Indonesian Parliament in implementing the Law on State Finance enacted in 2003. This paper shows that the Law’s requirement that the appropriation of annual budget is provided at the detailed activity level is not supportive of the government goal to reduce corruption. On the contrary, it has led to more corruption committed by the parliament members, and to undue disbursement delays. The resulting budget rigidity is also not supportive of the government objective to increase efficiency and effectiveness in the financial management through Performance-Based Budgeting and Medium Term Expenditure Framework (MTEF).